Retroperitoneal Bronchogenic Cyst Originating from Diaphragmatic Crura - Herek, Duygu (Indian J Surg, 2014)
Bronchogenic cyst is a benign lesion which is commonly seen in the posterior mediastinum. Diaphragmatic origin in retroperitoneum is an unusual location for a bronchogenic cyst. Cross-sectional imaging modalities describe the origin and content of the cyst evidently. Magnetic resonance (MR) images of a 42-year-old male patient who attended ER with back pain revealed a huge retroperitoneal complicated bronchogenic cyst arising from the diaphragm and surrounding the abdominal aorta anteriorly. Bronchogenic cysts in the retroperitoneum rarely originate from the diaphragm and should be kept in mind in the differential diagnoses of abdominal cystic lesions. MR imaging (MRI) is superior to other imaging techniques such as computerized tomography (CT) in detecting the origin and content of these cystic lesions.